The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s40830-016-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiopaque Shape Memory Alloys: NiTi–Er with Stable Superelasticity

Abstract: Binary NiTi alloy is one of the most important biomaterials currently used in minimally invasive procedures and indwelling devices. The poor visibility of intermetallic NiTi under X-ray could be an unsatisfactory feature especially for developing low-dimensional implantable devices for the body. It is a matter of fact that the alloying of a third radiopaque element, such as noble or heavy metals, in NiTi can significantly enhance the alloy's radiopacity. Recently, it was demonstrated that the addition of a rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The density for α-Bi 2 O 3 , β-Ta 2 O 5 , and β-Bi 7.8 Ta 0.2 O 12.2 is 9.37, 8.31, and 9.18 g/cm 3 , respectively. The measured radiopacity did not follow the expected rule [ 26 ]. It is suggested that, in addition to the composition, the particle size distribution at various stages may affect the solidification of MTA-like cements and the radiopacity performance.…”
Section: Resultsmentioning
confidence: 99%
“…The density for α-Bi 2 O 3 , β-Ta 2 O 5 , and β-Bi 7.8 Ta 0.2 O 12.2 is 9.37, 8.31, and 9.18 g/cm 3 , respectively. The measured radiopacity did not follow the expected rule [ 26 ]. It is suggested that, in addition to the composition, the particle size distribution at various stages may affect the solidification of MTA-like cements and the radiopacity performance.…”
Section: Resultsmentioning
confidence: 99%
“…They usually situate into the stenosis supply route decisively on the demonstration of x‐ray fluoroscopy. The representation and following of stents under fluoroscopy, which is the most certain methodology for perception, is achieved either through the stent‘s innate retention of x‐rays or by the situation of radiopaque markers on the stent [146].…”
Section: Methods Applied On the Metal Surfacementioning
confidence: 99%
“…The photoelectron effect arising from the interaction of X-ray photos with inner-shell electrons is the dominant factor [21]. Radiopacifiers with high atomic number (Z) improve radiopacity by increasing the mass attenuation coefficient (µ) in accordance with the power law of µ ∞ Z 3 [22]. It shows almost no scattering radiation and results in a high-quality image.…”
Section: Introductionmentioning
confidence: 99%